Concentration and pH Influence on the Reducing Property of Silk Fibroin from Silk Fibrous Waste in the Green Synthesis of Silver Nanoparticles - Wilson Agudelo; Yuliet Montoya; Alejandra Garcia-Garcia; John Bustamante (Journal of Nanotechnology)
The development of methods of green synthesis of metal nanoparticles from the use of biological agents, and microbial or plant extracts, allows the obtainment of biocompatible nanostructures by reducing or eliminating the use of toxic substances. On that basis, this research focused on evaluating the influence of silk fibroin from silk fibrous waste (SFw) on the synthesis of silver nanoparticles (AgNPs), by varying the concentrations of the precursor and reducing agent, as well as the change in the pH value of the reaction. The nanostructures were characterized by UV-visible spectrophotometry, scanning transmission electron microscopy (STEM) and transmission electron microscopy (TEM), zeta potential, and Fourier transform infrared spectroscopy (FTIR) with an ATR module. The results showed that SFw behaves as a reducing matrix and micellar structure, which favored the formation and obtainment of silver nanoparticles with colloidal stability, particle diameters, and defined morphologies. These aspects were evidenced through the identification of the characteristic surface plasmon resonance of the silver ion, the determination of the particle diameter, the electrokinetic potential, and the identification of the functional groups because of the oxidation of the reducing agent.